Comparing the Effect of Two Methods of Distraction and Touch on Intensity of Pain Related to Venipuncture in 5-10 Years Old Children - Razaghi N; Givari A; Tatarpoor P; Hoseini AF (Iran University of Medical Sciences, 2012)
Background & Aims : The pain related to invasive procedures such as venipuncture, causes physical and psychological stress in children and therefore should be given relief . Methods that reduce the pain related to invasive procedures in children are among the major priorities in nursing profession. This study compared the effect of two methods of distraction and touch on pain in 5-10 years old children.   Material & Methods: It was a randomized clinical trial. One hundred and twenty children , hospitalized in education al hospitals affiliated to Tehran University of Medical Sciences were randomly assigned to three groups of bubble blowing , touch and control. The first group was encouraged to play with bubbles before and during venipuncture the second group received touch peripheral to injection area before and during venipuncture and the third group received routine care . Immediately after injection, pain intensity was assessed by Wong-Baker faces scale. The data were analyzed by Chi-square , ANOVA , and Shefeh tests using SPSS-PC (v. 11).   Results : The findings showed that the mean score of pain intensity in bubble making group, touch group, and control group was 5.77 , 5.95 and 8.12 respectively. ANOVA test results showed that there is a significant difference between the mean score of pain intensity in control group and touch and bubble making groups (P=0.00). No significant difference was found between the pain intensity of bubble making and touch groups (P=0.89). Conclusion: Distraction and touch are effective methods for reducing injection pain in children. These procedures are among easy to use and practical nursing interventions that help children to cope with this common painful experience.